Lumbar drain associated radiculoplexopathy in a patient with spontaneous cerebrospinal fluid rhinorrhea: a proposed checklist - Chowdhary, Stuti; Cherian, Lisa Mary; Thomas, Naveen Kuriakose; Kurien, Regi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Continuous lumbar drainage (LD) is often performed along with endoscopic cerebrospinal fluid (CSF) rhinorrhoea repair. They serve various functions, such as offsetting the pressure over the repair site, decreasing the CSF pressure gradient across the repair site, and facilitating graft adhesion. However, their insertion may cause neurological sequelae due to displacement, breakage, or dural trauma at the site. The authors present a case of a rare complication of LD insertion where the patient developed lumbar plexus neuropathy due to an epidural CSF collection. Imaging and neurological assessment helped with the diagnosis, while device removal with bed rest resolved the symptoms. There is a paucity of literature on this complication in adults, and this report describes the presentation, management, and treatment of this problem along with a suggested checklist.